Jejunal diverticular perforation: a masquerader in the elderly during COVID era - Shajini, N.; Senthilkumar, M. (International Surgery Journal, 2022)
Jejunal pseudo-diverticulosis is a rare, acquired condition. In this era of COVID-19 pandemic, although there is insufficient data to suggest causation, gastro-intestinal complications of it have been reported. Being associated with high mortality, our case sheds light onto a potential gastrointestinal manifestation of COVID-19 and implicates the need for a high clinical suspicion of complicated jejunal diverticulosis in the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) positive elderly presenting with acute abdomen, having had long-term non-specific symptoms.